Food Security Versus Environmental Health: The Nitrogen Dilemma - Henrike Mielenz; Norbert Bischoff; Klaus Butterbach‐Bahl; Uwe Häußermann; Kurt‐Christian Kersebaum; Karin Rather; Burkhard Stever‐Schoo; Reinhard Well; Claas Nendel (Journal of Plant Nutrition and Soil Science, 2026)
ABSTRACT Nitrogen is an essential element for plant growth and, consequently, crop production. However, the cycling of nitrogen in the environment can have negative effects. Here, we review the historical development of scientific and public awareness of these effects and the influence this has had on political action to control them. Focusing on Germany as an example, we explore past nitrogen myths and how scientific progress has dispelled them, contextualizing our current position as a society seeking sufficient food, a clean environment, and an end to climate change. Given the continuous heavy burden placed on farmers to solve all these issues, we argue that from the state that we have reached today, further reducing nitrogen inputs for crop production may not necessarily lead to a further reduction in nitrogen cycling in the environment but rather to reductions in yields and product quality. Nevertheless, there is still potential to improve the efficiency of nitrogen use for stabilizing crop yields and to increase resilience against potential harm to the environment and human health. We make a couple of suggestions about what can be done.